A new index for hydrochar based on fixed carbon content to predict its structural properties and thermal behavior. (15th August 2021) - Tu, Ren; Sun, Yan; Wu, Yujian; Fan, Xudong; Cheng, Shuchao; Jiang, Enchen; Xu, Xiwei
Abstract: Biomass is an important source for the preparation of nanocarbon materials. And hydrothermal carbonization is also used to prepare carbon materials with rich functional groups. In this paper, the correlation between the degree of hydrothermal carbonization and the structure of hydrochar obtained from camellia shell, rice husk and tobacco stem were studied by establishing a mathematical relationship between the fixed carbon index (FCI) and the fiber content, functional group strength, specific surface area, average particle size and initial pyrolysis temperature of hydrochar, respectively. The results showed that the lignin content was linearly increased with the FCI. The decomposition order of biomass was followed by dehydration of cellulose and hemicellulose, demethylation cracking, lignin oxidation, polycondensation of cellulose and hemicellulose products, and lignin cleavage reaction with the increase of FCI. The specific surface area of hydrochar increased linearly from 0.28 m 2 /g to 25.09 m 2 /g, while the particle size of hydrogenated carbon decreased more slowly. The initial pyrolysis temperature of hydrochar had the lowest value (125°C–147 °C) when the FCI was around 0.5. Hydrothermal carbonization can reduce the activation energy of hemicellulose and cellulose. Graphical abstract: Image 1 Highlights: Established a correlation between fixed carbon index (FCI) and characteristics of hydrochar. The decomposition of fiber component is changed with the FCI. The BET of hydrochar increased linearly with the FCI (from 0.28 m 2 /g to 25.09 m 2 /g). Hydrothermal carbonization can reduce the activation energy of hemicellulose and cellulose. When FCI is at 0.5, biomass is most prone to pyrolysis.